2020
DOI: 10.1097/aog.0000000000003795
|View full text |Cite
|
Sign up to set email alerts
|

Mature Follicle Count and Multiple Gestation Risk Based on Patient Age in Intrauterine Insemination Cycles With Ovarian Stimulation

Abstract: OBJECTIVE: To estimate the risk of a multiple gestation pregnancy in ovarian stimulation intrauterine insemination (IUI) cycles when stratified by patient age and mature follicle number. METHODS: We conducted a retrospective cohort study at a single private practice fertility center of IUI cycles performed from 2004 to 2017. Intervention(s) were ovarian stimulation and IUI if postwash total motile sperm count was more than 8 million. Mature follicles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Additionally, Evans et al [ 24 ] also reported that the mean clinical pregnancy rate per IUI ranged from 13.0% with one mature follicle to 19.6% with five mature follicles. The pregnancy rate increased modestly with the presence of each additional mature follicle (adjusted odds ratio: two follicles vs. one: 1.3, 95% CI 1.2–1.4; three follicles vs. one: 1.4, 95% CI 1.3–1.5; four follicles vs. one: 1.5, 95% CI 1.4–1.7; and five follicles vs. one: 1.6, 95% CI 1.4–1.9).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Evans et al [ 24 ] also reported that the mean clinical pregnancy rate per IUI ranged from 13.0% with one mature follicle to 19.6% with five mature follicles. The pregnancy rate increased modestly with the presence of each additional mature follicle (adjusted odds ratio: two follicles vs. one: 1.3, 95% CI 1.2–1.4; three follicles vs. one: 1.4, 95% CI 1.3–1.5; four follicles vs. one: 1.5, 95% CI 1.4–1.7; and five follicles vs. one: 1.6, 95% CI 1.4–1.9).…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 14 According to 2017 Society for Assisted Reproductive Technology data, only 2.5% of IVF cycles are performed in patients diagnosed with endometriosis, leading us to believe that endometriosis is grossly underdiagnosed in the setting of infertility. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Although non-significant, the CPR was higher in multi-follicular development than mono-follicular development in both CC-IUI and rFSH-IUI cycles (Berker et al, 2011). Evans et al (2020) defined the mature follicles as a follicle size above 14 mm, and they found increasing pregnancy rates with increased number of mature follicles. Moreover, they showed higher multiple gestations with this increase.…”
Section: Discussionmentioning
confidence: 93%
“…However, the follicle sizes on the day of hCG were not homogeneous (van Rumste et al, 2008). Evans et al (2020) recently concluded that two preovulatory follicles improved the pregnancy rates, but more than two follicles did not contribute the chance of singleton pregnancy. We excluded the cycles that had more than two preovulatory follicles (>17 mm) and found that bi-follicular growth significantly increased the clinical pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%